Pencegahan radikalisme di kalangan remaja melalui Pembelajaran PPKn - Nurkhalisha Salsabila; Maria Montessori; Junaidi Indrawadi; Tetti Eka Purnama (Departemen Pendidikan Kewarganegaraan dan Ilmu Hukum Universitas Negeri Padang, 2026)
This study is motivated by the increasing potential spread of radicalism among adolescents, which may influence students’ cognitive patterns, attitudes, and behaviors. Schools, as formal educational institutions, play a strategic role in preventing the development of radical ideologies, particularly through Civic Education (PPKn). This study aims to describe the implementation of radicalism prevention among adolescents through PPKn learning at SMAS Nurul Ikhlas X Koto, Tanah Datar Regency, and to identify the supporting factors in its implementation. This research employs a qualitative approach with a descriptive design. Informants were selected using purposive sampling, consisting of PPKn teachers, the principal, vice principals in curriculum and student affairs, and students. Data were collected through observation, interviews, and documentation studies, including lesson plans (RPP) and school regulations. Data analysis was conducted through data reduction, data display, and conclusion drawing. The findings indicate that radicalism prevention is implemented through democratic learning practices, the modeling of moderate attitudes, respect for students’ opinions, the internalization of anti-radical values, and the prevention of student grouping based on particular viewpoints. In addition, supporting factors include an open and inclusive school environment, the application of universal values, the involvement of alumni and parents, and sustained communication. These findings suggest that PPKn learning functions as a strategic medium for character formation and the strengthening of students’ tolerance, thereby contributing to the prevention of radicalism among adolescents.